Dampak Pernikahan dibawah Umur Terhadap Keharmonisan Rumah Tangga di Desa Badegan Kecamatan Badegan Kabupaten Ponorogo - Mutrofin, Siti; Kadenun, Kadenun; Fathoni, Khoirul (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Marriage is a sacred bond between a man and a woman as husband and wife with the aim of forming a sakinah family, so that marriage towards a sakinah family requires not only physical and mental preparation but also socio-economic, emotional and responsibility readiness. Thus limiting the age of marriage is one of the important principles because the Marriage Law is already regulated and clear. However, in Badegan Village, Badegan District, Ponorogo Regency, there are still many underage marriages which will have an impact on the harmony of a household. With a qualitative descriptive approach, this journal will describe some of the data obtained from the field, both by interviews, observation, and documentation as a data collection method, then proceed with the process of data reduction, data presentation and drawing conclusions using data analysis methods. In addition, the data analysis process is also supported by literature review as a reference to strengthen data obtained from the field. From the results of this study it can be concluded that the factors that cause underage marriages in Badegan Village, Badegan District, Ponorogo Regency are pregnancies outside of marriage which are influenced by the lack of parental supervision and the willingness of the child itself. So that underage marriages have a great impact on household harmony because maturity and personal integrity are not stable in resolving existing problems. Some of the impacts of underage marriages are the increased burden on parents, lack of independence and divorce.